The influence of type 2 diabetes on fibrin clot properties in patients with coronary artery disease - Neergaard-Petersen, Søs; Hvas, Anne-Mette; Kristensen, Steen D.; Grove, Erik L.; Larsen, Sanne B.; Phoenix, Fladia; Kurdee, Zeyad; Grant, Peter J.; Ajjan, Ramzi A. (Thrombosis and Haemostasis, 2014)
Type 2 diabetes mellitus (T2DM) increases the risk of coronary thrombosis and both conditions are associated with altered fibrin clot properties. However, the influence of T2DM on fibrin clot properties in patients with coronary artery disease (CAD) remains unclear. We aimed to investigate the influence of T2DM on fibrin clot properties in patients with CAD. Fibrin clot structure and fibrinolysis were investigated in 581 CAD patients (148 with T2DM) using turbidimetric assays, confocal and scanning electron microscopy. Clots made from plasma and plasma-purified fibrinogen were studied, and plasma levels of inflammatory markers were analysed. T2DM patients had increased clot maximum absorbance compared with non-diabetic patients (0.36 ± 0.1 vs 0.33 ± 0.1 au; p=0.01), displayed longer lysis time (804 [618;1002] vs 750 [624;906] seconds; p=0.03) and showed more compact fibrin structure assessed by confocal and electron microscopy. Fibrinogen levels were elevated in T2DM (p< 0.001), but clots made from purified fibrinogen showed no differences in fibrin properties in the two populations. Adjusting for fibrinogen levels, T2DM was associated with C-reactive protein and complement C3 plasma levels, with the former correlating with clot maximum absorbance (r=0.24, p< 0.0001) and the latter with lysis time (r=0.30, p< 0.0001). Independent of fibrinogen levels, females had more compact clots with prolonged lysis time compared with males (all p-values< 0.001). In conclusion, T2DM is associated with prothrombotic changes in fibrin clot properties in patients with CAD. This is related to quantitative rather than qualitative changes in fibrinogen with a possible role for inflammatory proteins.
Keywords: Fibrin clot; fibrinolysis; coronary artery disease; type 2 diabetes mellitus; inflammation